β-catenin signaling, the constitutive androstane receptor and their mutual interactions - Braeuning, Albert; Pavek, Petr (Archives of toxicology, 2020)
Aberrant signaling through β-catenin is an important determinant of tumorigenesis in rodents as well as in humans. In mice, xenobiotic activators of the constitutive androstane receptor (CAR), a chemo-sensing nuclear receptor, promote liver tumor growth by means of a non-genotoxic mechanism and, under certain conditions, select for hepatocellular tumors which contain activated β-catenin. In normal hepatocytes, interactions of β-catenin and CAR have been demonstrated with respect to the induction of proliferation and drug metabolism-related gene expression. The molecular details of these interactions are still not well understood. Recently it has been hypothesized that CAR might activate β-catenin signaling, thus providing a possible explanation for some of the observed phenomena. Nonetheless, many aspects of the molecular interplay of the two regulators have still not been elucidated. This review briefly summarizes our current knowledge about the interplay of CAR and β-catenin. By taking into account data and observations obtained with different mouse models and employing different experimental approaches, it is shown that published data also contain substantial evidence that xenobiotic activators of CAR do not activate, or do even inhibit signaling through the β-catenin pathway. The review highlights new aspects of possible ways of interaction between the two signaling cascades and will help to stimulate scientific discussion about the crosstalk of β-catenin signaling and the nuclear receptor CAR.
Keywords: nádorová transformace buněk; hodnocení rizik; Wnt Signaling Pathway; Wnt signaling; Risk Assessment; Risk Factors; Receptors, Cytoplasmic and Nuclear; xenobiotika; Liver tumor promotion; beta Catenin; Cell Transformation, Neoplastic; Constitutive Androstane Receptor; Animals; lidé; konstitutivní androstanový receptor; Drug metabolism; játra; Humans; Xenobiotics; zvířata; Hepatocyte; rizikové faktory; Nuclear receptor; Liver; Liver Neoplasms; signální dráha Wnt; receptory cytoplazmatické a nukleární; nádory jater; beta-katenin